Investigation of the Aztec Law and Its Basic Problems - Peter Vyšný (Societas et Iurisprudentia, 2015)
The term “Aztecs” is being mostly used as a collective name of the inhabitants of three in the Valley of Mexico (in Central Mexico) situated allied prehispanic city-states Tenochtitlan, Texcoco, and Tlacopan. Although in recent decades various aspects of the Aztec culture have been intensively researched, no systematic interest awakened for the Aztec law. The study deals with the current state of research of the Aztec law, the written and unwritten sources of its knowledge, its fundamental characteristics as a research object, and its social and cultural-historical context. The paper shows that a systematic research of the Aztec law should focus not only on the Aztec law as such, but also on its social, economic, political, and cultural contexts as well as on the Aztec worldview (ideology, religion).